Identification and characterization of N6-methyladenosine circular RNAs in the spinal cord of morphine-tolerant rats - Xing, Manyu; Deng, Meiling; Shi, Yufei; Dai, Jiajia; Ding, Tong; Song, Zongbin; Zou, Wangyuan (Frontiers in Neuroscience, 2022)
Morphine tolerance (MT) is a tricky problem, the mechanism of it is currently unknown. Circular RNAs (circRNAs) serve significant functions in the biological processes of the central nervous system. N6-methyladenosine (m6A), as a key post-transcriptional modification of RNA, can regulate the metabolism and functions of circRNAs. Here we explore the patterns of m6A-methylation of circRNAs in the spinal cord of morphine-tolerant rats. In brief, we constructed a morphine-tolerant rat model, performed m6A epitranscriptomic microarray using RNA samples collected from the spinal cords of morphine-tolerant rats and normal saline rats, and implemented the bioinformatics analysis. In the spinal cord of morphine-tolerant rats, 120 circRNAs with different m6A modifications were identified, 54 of which were hypermethylated and 66 of which were hypomethylated. Functional analysis of these m6A circRNAs found some important pathways involved in the pathogenesis of MT, such as the calcium signaling pathway. In the m6A circRNA-miRNA networks, several critical miRNAs that participated in the occurrence and development of MT were discovered to bind to these m6A circRNAs, such as miR-873a-5p, miR-103-1-5p, miR-107-5p. M6A modification of circRNAs may be involved in the pathogenesis of morphine tolerance. These findings may lead to new insights into the epigenetic etiology and pathology of morphine tolerance.